Patient Sex Is a Significant Factor in Arm Function Recovery After Arthroscopic Rotator Cuff Repair - Hirotomo Shibahashi, O.T.R., Ph.D; Miyuki Murakawa, O.T.R., Ph.D; Issei Yuki, M.D; Tomohiro Uno, M.D., Ph.D; Yuya Takakubo, M.D., Ph.D; Michiaki Takagi, M.D., Ph.D (Elsevier, 2024)
Purpose: To investigate the impact of patient sex on arm functional recovery after arthroscopic rotator cuff repair (ARCR). Methods: We retrospectively reviewed the clinical records of patients who underwent rehabilitation after ARCR at two affiliated hospitals between January 2014 and December 2019. Patient characteristics included age, sex, type of muscle tear, tear location, muscle strength, Japanese Orthopedic Association (JOA) score, and patient responses to the Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) questionnaire. We used mixed-effects regression models with random intercepts to evaluate the QuickDASH scores, JOA scores, and muscle strength relative to the nonoperated side. Results: Of the 124 patients, 82 (66.1%) were 65-year-old men and 42 (33.9%) were 67-year-old women. The preoperative JOA scores (P = .03) and those at 6 months (P < .001) and 12 months (P = .04) after ARCR were significantly greater for men than for women. QuickDASH scores of men were significantly lower at 24 months (P = .02) and all other time points (P < .001) than those of women. The improvement in QuickDASH scores was significantly higher for women than for men (P < .01). The results of the multiple regression analysis showed that patient sex (95% confidence interval, 0.01-0.45; P < .05) had an impact on QuickDASH scores at 24 months after ARCR. Conclusions: In this study, patient sex was a significant factor affecting the recovery and QuickDASH scores of patients who underwent ARCR. Level of Evidence: Level IV, prognostic case series.